Financial modeling - Sengupta, Chandan
This book, designed for self-study, classroom use, and reference, presents a com-prehensive approach to developing simple to sophisticated financial models in all major areas of finance. The approach is based on the author's 20 years of experience of developing such models in the business world and teaching a popular MBA class in financial modeling